Applying ISO/IEC 25010 standard to prioritize and solve quality issues of automatic ETL processes - Alves, T.; Lopes, P.; Dias, J. (Proceedings 30th International Conference on Software Maintenance and Evolution ICSME 2014, 2014)
The goal of any automatic process is to run without human intervention. However, it is not uncommon that unexpected issues recur, requiring repetitive human intervention in order to processes execute successfully. Such situations indicate that those processes were not designed with the necessary quality requirements to achieve the automation goal, and quality needs to be improved. This paper describes a case study of the quality improvements of several automatic ETL processes that required a growing amount of effort to ensure its successful execution. Key to the improvement process was the use of the ISO/IEC 25010 Standard for Systems and Software Quality Requirements and Evaluation to categorize all issues found. This approach proved beneficial in two important ways: first, it created a clear understanding of the overall ETL processes quality problems, second, it made obvious which issues deserved uttermost attention.